Plasmacytoid variant of bladder cancer defines patients with poor prognosis if treated with cystectomy and adjuvant cisplatin-based chemotherapy - Keck, Bastian; Wach, Sven; Stöhr, Robert; Kunath, Frank; Bertz, Simone; Lehmann, Jan; Stöckle, Michael; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt (BMC Cancer, 2013)
Background: Since the definition of different histologic subtypes of urothelial carcinomas by the World Health Organization (WHO) 2004 classification, description of molecular features and clinical behavior of these variants has gained more attention.Methods: We reviewed 205 tumor samples of patients with locally advanced bladder cancer mainly treated within the randomized AUO-AB05/95 trial with radical cystectomy and adjuvant cisplatin-based chemotherapy for histologic subtypes. 178 UC, 18 plasmacytoid (PUC) and 9 micropapillary (MPC) carcinomas of the bladder were identified. Kaplan Meier analysis and backward multivariate Cox's proportional hazards regression analysis were performed to compare overall survival between the three histologic subtypes.Results: Patients suffering from PUC have the worst clinical outcome regarding overall survival compared to conventional UC and MPC of the bladder that in turn seem have to best clinical outcome (27.4 months, 62.6 months, and 64.2 months, respectively; p=0.013 by Kaplan Meier analysis). Backward multivariate Cox́s proportional hazards regression analysis (adjusted to relevant clinicopathological parameters) showed a hazard ratio of 3.2 (p=0.045) for PUC in contrast to patients suffering from MPC.Conclusions: Histopathological diagnosis of rare variants of urothelial carcinoma can identify patients with poor prognosis. © 2013 Keck et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2025-08-19
Keywords: ChemotherapyCystectomyMicropapillaryPlasmacytoidPrognosis; Urinary bladder neoplasm